Analysis of Character Education in The Sansho Dayu Movie - Muhammad Hauzan A.; Ulfah Sutiyarti (Jurnal Konsepsi, 2022)
The Sansho Dayu movie was a movie from the 1940’s bringing the jidai-geki theme which involves old feudal Japan. The story behind the movie itself came from a self-titled children’s fairytale that has been around since the 14th or 15th century, that was later adapted into a movie director’s work of Kenzo Mizoguchi. Despite its realist approach to the movie in which Mizoguchi even consulted a historian amongst his script writers and incorporating the land lordship and culture of the Japanese Heian era, Mizoguchi’s take on the film did not forget the story’s moral based of the source material. Qualitative is used in this research. In data analysis, researchs used constructivism theory. Research results shows that the Sansho Dayu movie contains character education, which is but not limited to altruism, mutual cooperation, empathizing, cooperative, and determinative.